Perkembangan Hukum pidana Islam Di Era Reformasi Menuju Univikasi Hukum Indonesia - Munkizul Umam Kau (JURNAL LEGALITAS, 2009)
Basically, even constitutionally Islam is not legal as state religion, but in reality, Indonesia state has many adopting Islam principles in our life, nation and societal. Thereby it\'s fair if islam criminal law that written in tadition of Islam and has been applied at Islam state in world, applied also in Indonesia. Applying of Islam crime law utterly, as wanted by Islam thinkers, likely difficult to be done in Indonesia, and if happened only miracle which can answer it. However contribution of Islam criminal law in positive law image cannot be overrulerd off hand.many things which only be recognized in islam crime law then strats recognized in our positive law. Kata Kunci: Perkembangan, hukum, pidana, Islam, Univikasi.